MEMAHAMI KOMUNIKASI MELALUI PENELITIAN - Wisri Wisri; Abd. Mughni (LP2M Universitas Ibrahimy, 2018)
Communication is central in human life. All activities in human life require communication. The scientific study of the symptoms or reality of communication covers a very broad field, covering all forms of human relations and using symbols. more concretely this includes fields such as Interpersonal Communication, Group Communication, Organizational/Intellectual Communication, Mass Communication and Cultural Communication as seen in various forms of symbolic expression. Noting the seven traditions of communication research as such, communication research seems to be facing an important issue for its development in the present and future, which is pleased with how to try to take steps to get out of the confines of tradition and / or bring together existing traditions. This effort might be in the form of combining one tradition with another existing tradition (trying to synthesize existing traditions) while pioneering an entirely new tradition, for example with a more extensive implementation of historical methods to discover how communication patterns exists in a society in the past and attempts to understand what is now by looking at the past.